Composite particles and method for producing the same

JP7635628B2Active Publication Date: 2025-02-26DIC CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021077406
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-30
Publication Date
2025-02-26
Estimated Expiration
2041-04-30

AI Technical Summary

Benefits of technology

【0023】 本発明によれば、酸化モリブデンで構成される無機被覆部を有し、良好な諸特性を発現可能な複合粒子を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007635628000002
    Figure 0007635628000002
  • Figure 0007635628000003
    Figure 0007635628000003
  • Figure 0007635628000004
    Figure 0007635628000004
Patent Text Reader

Abstract

To provide composite particles having an inorganic coating composed of a molybdenum compound and capable of exhibiting good properties.SOLUTION: Composite particles comprise alumina particles containing molybdenum (Mo) and an inorganic coating formed on the surface of the alumina particles and composed of molybdenum oxide, and the ratio of the amount of MoO3 to the amount of Al2O3 at the surface of the alumina particles ([MoO3] / [Al2O3]×100)XPS is equal to or more than 15.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to composite particles and a method for producing the composite particles, and in particular to composite particles in which an inorganic coating portion is provided on an alumina particle. [Background technology]

[0002] Alumina has many applications due to its excellent mechanical strength including abrasion resistance, chemical stability, thermal conductivity, heat resistance, etc., and is used in a wide range of areas such as pigments, paints, coatings, abrasives, electronic materials, heat dissipation fillers, optical materials, cosmetics, biomaterials, etc. As a conventional technique, for example, an adsorbent for metallic mercury in exhaust gas in which 5 atom % or more of molybdenum trioxide or tungsten trioxide is supported on an inert carrier such as silica, titania, alumina, or zirconia is disclosed (Patent Document 1).

[0003] The present applicant has discovered that it is possible to manufacture plate-like α-alumina with a narrow particle size and particle size distribution by using MoO3 as a flux agent and adding silica or germanium, and has disclosed this technology (Patent Document 2).

[0004] In addition, molybdenum trioxide (MoO3) is widely used as a catalyst, optical material, pigment, additive for ceramics and glass manufacturing, semiconductor, etc. The applicant of the present invention discovered that nano-MoO3 can be synthesized by quenching MoO3 vapor, and has disclosed this technology (Patent Document 3). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2008-238057 A [Patent Document 2] JP 2016-222501 A [Patent Document 3] International Publication No. 2018 / 003481 Summary of the Invention [Problem to be solved by the invention]

[0006] However, in the adsorbent of Patent Document 1, the particle size of alumina and the structural positional relationship between the inactive alumina carrier and molybdenum trioxide are unclear, and there is still room for improvement in order to enhance the various properties exhibited by molybdenum trioxide. In addition, the adsorbent of Patent Document 1 adsorbs metallic mercury in exhaust gas, and its applications are limited. Moreover, none of Patent Documents 2 and 3 discloses any knowledge about composite particles having alumina particles and a coating portion made of molybdenum oxide, or about the characteristics thereof.

[0007] The present invention has been made in consideration of the above circumstances, and has an object to provide composite particles having an inorganic coating portion composed of molybdenum oxide and capable of exhibiting various favorable characteristics, and a method for producing the composite particles. [Means for solving the problem]

[0008] As a result of intensive research to solve the above problems, the present inventors have found that when a molybdenum compound is further added to alumina particles containing molybdenum and then calcined, the alumina particles are easily covered with molybdenum oxide, and the molybdenum oxide can be unevenly distributed on the surfaces of the alumina particles, and have completed the present invention. In addition, a very low pH is obtained in, for example, an aqueous solvent by combining alumina particles containing molybdenum with molybdenum oxide unevenly distributed on the surfaces of the alumina particles, and therefore it is expected that various properties derived from molybdenum oxide, including antibacterial and antiviral functions and oxidation catalyst functions, can be expressed.

[0009] That is, the present invention provides the following means. [1] Alumina particles; and an inorganic coating portion formed on the surface of the alumina particles and composed of molybdenum oxide; The ratio of the amount of MoO3 to the amount of Al2O3 on the surface of the alumina particles ([MoO3] / [Al2O3]×100) obtained by X-ray photoelectron spectroscopy (XPS) analysis XPSis 15 or more, a composite particle.

[0010] [2] The ratio of the amount of MoO3 to the amount of Al2O3 in the alumina particles ([MoO3] / [Al2O3]×100) obtained by X-ray fluorescence (XRF) analysis. XRF is 1 or more, ([MoO3] / [Al2O3] x 100) XPS ([MoO3] / [Al2O3]×100) XRF The composite particle according to [1] above,

[0011] [3] The composite particle according to the above [1] or [2], wherein the alumina particle has an alpha crystallization rate of 90% or more.

[0012] [4] The composite particles according to any one of the above [1] to [3], wherein the alumina particles contain molybdenum.

[0013] [5] The composite particle according to any one of the above [1] to [4], wherein the alumina particles have a plate shape, a thickness of 0.01 μm or more and 5 μm or less, an average particle diameter of 0.1 μm or more and 500 μm or less, and an aspect ratio of 2 or more and 500 or less.

[0014] [6] The composite particle according to [1] above, wherein the alumina particle further contains silicon and / or germanium.

[0015] [7] The composite particle according to [6] above, wherein the alumina particle contains mullite in a surface layer.

[0016] [8] A composite particle comprising the composite particle according to any one of [1] to [7] above.

[0017] [9] A step of producing alumina particles by calcining a first mixture containing an aluminum compound containing an aluminum element and a molybdenum compound containing a molybdenum element, or a first mixture containing an aluminum compound containing an aluminum element, a molybdenum compound containing a molybdenum element, and a shape control agent for controlling the shape of alumina particles; a step of firing a second mixture containing the alumina particles and a molybdenum compound containing elemental molybdenum to form an inorganic coating portion composed of a molybdenum compound on the surface of the alumina particles; A method for producing composite particles, comprising:

[0018]

[10] The method for producing composite particles according to the above [9], wherein the molybdenum compound is molybdenum oxide.

[0019]

[11] The method for producing composite particles according to

[10] above, wherein in the step of forming the inorganic coating portion, the second mixture is fired at 750°C or higher and lower than 1100°C.

[0020]

[12] The method for producing composite particles according to

[10] above, wherein in the step of producing the alumina particles, the first mixture is fired at 900° C. or higher.

[0021]

[13] The method for producing composite particles according to any one of the above [9] to

[12] , wherein the shape control agent is composed of one or more selected from silicon, a silicon compound containing silicon element, and a germanium compound containing germanium element.

[0022]

[14] The method for producing composite particles according to any one of the above [9] to

[13] , wherein the first mixture further contains a potassium compound containing elemental potassium. Effect of the Invention

[0023] According to the present invention, it is possible to provide composite particles which have an inorganic coating portion made of molybdenum oxide and are capable of exhibiting various favorable characteristics. [Brief description of the drawings]

[0024] [Figure 1] FIG. 1 is a scanning electron microscope image showing the composite particle obtained in Example 1 as an example of the configuration of the composite particle according to an embodiment of the present invention. [Diagram 2]FIG. 2 is a scanning electron microscope image showing the composite particle obtained in Example 4 as an example of the configuration of the composite particle according to an embodiment of the present invention. [Diagram 3] FIG. 3 is a scanning electron microscope image showing the alumina particles obtained in Comparative Example 1 as an example of the configuration of a comparative example of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings.

[0026] <Composite particles> The composite particle according to this embodiment includes an alumina particle and an inorganic coating portion formed on the surface of the alumina particle and composed of molybdenum oxide. The composite particle according to this embodiment may have any shape, such as a plate shape, a card house shape, or a polyhedron. From the viewpoint of making the most of the anisotropy of the composite particle, it is preferable that the composite particle has, for example, a plate shape. When the composite particle is formed in a plate shape, the alumina particle also has a plate shape. Hereinafter, in this embodiment, the alumina particle having a plate shape is also referred to as "plate-shaped alumina particle", "plate-shaped alumina", or simply "alumina particle".

[0027] <Plate-shaped alumina particles> In the present invention, "plate-like" refers to an aspect ratio of 2 or more, calculated by dividing the average particle diameter of the alumina particles by the thickness. In this specification, the "thickness of the alumina particles" refers to the arithmetic mean value of thicknesses measured for at least 50 plate-like alumina particles randomly selected from an image obtained by a scanning electron microscope (SEM). Also, the "average particle diameter of the alumina particles" refers to the volume-based median diameter D from a volume-based cumulative particle size distribution measured by a laser diffraction particle diameter measurement device. 50 The value calculated as follows.

[0028] In the case of alumina particles, the following conditions of thickness, particle size, and aspect ratio can be combined in any way as long as the alumina particles are plate-like. The upper and lower limit values ​​of the numerical ranges exemplified in these conditions can be freely combined.

[0029] The plate-like alumina particles preferably have a thickness of 0.01 μm or more and 5 μm or less, preferably 0.03 μm or more and 5 μm or less, more preferably 0.1 μm or more and 5 μm or less, more preferably 0.3 μm or more and 3 μm or less, and even more preferably 0.5 μm or more and 1 μm or less.

[0030] The plate-shaped alumina particles have an average particle diameter (D 50 ) is preferably 0.1 μm or more and 500 μm or less, more preferably 0.5 μm or more and 50 μm or less, and even more preferably 1 μm or more and 20 μm or less. The average particle size (D 50 Alumina particles having an average particle diameter (D) of at least the above lower limit are suitable for use as a filler, and when used as a functional filler, they can fully exhibit the antibacterial, antiviral, and other properties exhibited by the inorganic coating. 50 ) has low agglomeration properties and therefore has excellent dispersibility when used as a resin filler.

[0031] The aspect ratio of the plate-like alumina particles, which is the ratio of particle diameter to thickness, is preferably 2 to 500, more preferably 5 to 100, and even more preferably 10 to 50. When the aspect ratio of the plate-like alumina particles is 2 or more, it is preferable that the particles have two-dimensional blending characteristics, and when the aspect ratio of the plate-like alumina particles is 500 or less, it is preferable that the particles have excellent mechanical strength. When the aspect ratio is 5 or more, it is preferable that the above-mentioned characteristics can be more effectively exhibited.

[0032] The plate-like alumina particles may be in the form of a circular plate or an elliptical plate, but the particle shape is preferably, for example, a polygonal plate from the viewpoints of ease of handling and production.

[0033] The plate-like alumina particles may be obtained based on any manufacturing method, but it is preferable to obtain them by firing an aluminum compound in the presence of a molybdenum compound (preferably further a potassium compound) and a shape control agent, in terms of a higher aspect ratio, better dispersibility, and better productivity. The shape control agent is preferably at least one selected from the group consisting of silicon, a silicon compound, and a germanium compound. Since the shape control agent is a source of Si for mullite described later, it is more preferable to use silicon or a silicon compound containing silicon element. In the above manufacturing method, the molybdenum compound is used as a fluxing agent. In the present specification, this manufacturing method using a molybdenum compound as a fluxing agent may be simply referred to as the "flux method". The flux method will be described in detail later. It is considered that, after the molybdenum compound reacts with the aluminum compound at high temperature by the firing to form aluminum molybdate, the aluminum molybdate is further decomposed into alumina and molybdenum oxide at a higher temperature, and the molybdenum compound is taken into the plate-like alumina particles. The molybdenum oxide is sublimated, recovered, and can be reused. In addition, when the plate-like alumina particles contain mullite in the surface layer, it is considered that the silicon or silicon atom-containing compound blended as a shape control agent reacts with the aluminum compound via molybdenum during this process, forming mullite in the surface layer of the plate-like alumina particles. More specifically, the mechanism of mullite formation is that on the alumina plate surface, the reaction of molybdenum with Si atoms forms Mo-O-Si, and the reaction of molybdenum with Al atoms forms Mo-O-Al, and high-temperature firing causes Mo to be released and mullite having Si-O-Al bonds is formed. Molybdenum oxide that is not incorporated into the plate-like alumina particles is preferably recovered by sublimation and reused. In this specification, a material that has the property of being sublimable in the manufacturing method described below is called a fluxing agent, and a material that cannot be sublimated is called a shape control agent.

[0034] In the production of the plate-like alumina particles, by utilizing molybdenum and a shape control agent, the plate-like alumina particles have a high alpha crystal rate and are idiomorphic, thereby realizing excellent dispersibility, mechanical strength, and high thermal conductivity.

[0035] When the plate-like alumina particles contain mullite in the surface layer, the amount of mullite generated in the surface layer of the plate-like alumina particles can be controlled by the proportions of the molybdenum compound and the shape control agent used, and in particular, by the proportion of silicon or a silicon compound containing silicon used as the shape control agent. The preferred amount of mullite generated in the surface layer of the plate-like alumina particles and the preferred proportions of the raw materials used will be described in detail later.

[0036] From the viewpoint of further exhibiting the above-mentioned properties, the plate-like alumina particles are plate-like alumina particles having an aspect ratio of 5 to 500, and are solid. 27 In Al NMR analysis, the longitudinal relaxation time T1 for a peak of hexacoordinate aluminum at 10 to 30 ppm at a static magnetic field strength of 14.1 T is preferably 5 seconds or longer.

[0037] The longitudinal relaxation time T1 of 5 seconds or more means that the plate-like alumina particles have high crystallinity. It has been reported that the longer the longitudinal relaxation time in the solid state, the better the crystal symmetry and the higher the crystallinity (previously reported: Kitagawa Susumu et al., "Society of Coordination Chemistry Selection 4: Solution and Solid-State NMR of Multinuclear Species," Sankyo Publishing Co., Ltd., p. 80-82).

[0038] In the plate-like alumina particles, the longitudinal relaxation time T1 is preferably 5 seconds or more, more preferably 6 seconds or more, and even more preferably 7 seconds or more. In the plate-like alumina particles of the embodiment, the upper limit of the longitudinal relaxation time T1 is not particularly limited, but may be, for example, 22 seconds or less, 15 seconds or less, or 12 seconds or less. An example of the numerical range of the longitudinal relaxation time T1 exemplified above may be 5 seconds or more and 22 seconds or less, 6 seconds or more and 15 seconds or less, or 7 seconds or more and 12 seconds or less.

[0039] The plate-shaped alumina particles are solid 27 It is preferable that no peak of 4-coordinate aluminum is detected at 60 to 90 ppm in Al NMR analysis at a static magnetic field strength of 14.1 T. Such plate-like alumina particles are considered to be less susceptible to breakage or falling off due to distortion of crystal symmetry caused by the inclusion of crystals with different coordination numbers, and tend to have better shape stability.

[0040] Conventionally, the degree of crystallinity of inorganic materials is generally evaluated by the results of XRD analysis and the like. However, the inventors have found that, by using the longitudinal relaxation time T1 as an index for evaluating the crystallinity of alumina particles, more accurate analysis results can be obtained than with conventional XRD analysis. The plate-like alumina particles according to the embodiment have a long longitudinal relaxation time T1 of 5 seconds or more, and the crystallinity of the alumina particles can be said to be high. That is, the plate-like alumina particles according to the embodiment are probably highly crystallinity-prohibiting diffuse reflection on the crystal surface, improving light reflection, and providing excellent brilliance.

[0041] Furthermore, the present inventors have found that the value of the longitudinal relaxation time T1 is highly correlated with the shape retention rate of the plate-like alumina particles and the processing stability of the resin composition. In particular, in the case of plate-like alumina particles having an average particle diameter of 10 μm or less and an aspect ratio of 30 or less, the correlation between the value of the longitudinal relaxation time T1, the shape retention rate of the plate-like alumina particles, and the processing stability of the resin composition is significantly expressed. The above-mentioned plate-like alumina particles having the longitudinal relaxation time T1 of 5 seconds or more have the advantage that when blended with a resin to produce a resin composition, the processing stability is good and processing into a desired shape is easy. The above-mentioned plate-like alumina particles have a long value of the longitudinal relaxation time T1, so that the crystallinity is enhanced. Therefore, it is considered that the strength of the particles is high due to the high crystallinity of alumina, and when the resin and the plate-like alumina particles are mixed in the production process of the resin composition, the plate is unlikely to break, and further, it is considered that the particle surface has few irregularities due to the high crystallinity of alumina, and therefore has excellent adhesion to the resin. Due to these factors, it is believed that the above-mentioned plate-like alumina particles have good processing stability in resin compositions. Therefore, according to the composite particles having the above-mentioned plate-like alumina particles, even when they are blended into a resin composition, the inherent performance of the plate-like alumina particles and the inorganic coating portion is well exhibited.

[0042] The shape retention rate can be evaluated as follows. (shape retention rate) A total of 5 kg of mixture is prepared by mixing 66% by mass of alumina particles and 34% by mass of polyphenylene sulfite resin (PPS resin, DIC LR-100G). 5 kg of the mixture is melt-kneaded using a twin-screw extruder with a screw diameter of 40 mm and L / D=45 under the conditions of a feed rate of 15 kg / h, an extruder temperature of 320°C, and a screw rotation speed of 150 rpm. The strands obtained after melt mixing are cut using a pelletizer to obtain pellets with a major axis of 3 mm and a length of 5 mm. 5 g of the pellets are collected, placed in a crucible, and heated at 700°C for 3 hours to incinerate the pellets. The average particle diameter D of the incinerated powder sample is 50(μm) was measured using a laser diffraction particle size distribution analyzer, and the obtained value was taken as the average particle diameter after extrusion kneading. In addition to the above sample, 3 g of a sample before extrusion kneading (before being mixed with polyphenylene sulfite resin) was prepared, and the average particle diameter D 50 (μm) is measured in the same manner, and the obtained value is regarded as the average particle size before extrusion kneading. The shape retention rate (%) of the powder is calculated by (average particle size after extrusion kneading / average particle size before extrusion kneading×100). It is believed that in samples with low crystallinity, the alumina particles are destroyed by melt-kneading in the extruder, increasing the fine particle content, and the average particle size becomes smaller than before kneading (the shape retention value decreases).

[0043] The processing stability can be evaluated, for example, by the following method. (Processing stability) A total of 5 kg of a mixture was prepared by mixing 66% by mass of alumina particles and 34% by mass of polyphenylene sulfite resin (PPS resin, DIC, LR-100G). 5 kg of the mixture was melt-kneaded using a twin-screw extruder with a screw diameter of 40 mm and L / D=45 under the conditions of a feed rate of 15 kg / h, an extruder temperature of 320°C, and a screw rotation speed of 150 rpm. The strands coming out of the die were evaluated as having poor processing stability if their diameter was unstable and caused surging, or if unevenness or streaks were observed on the strand surface due to foaming or foreign matter, and those not observed were evaluated as having good processing stability.

[0044] It has been difficult to obtain plate-shaped alumina particles with high crystallinity compared to spherical alumina particles. This is believed to be because, unlike spherical alumina particles, plate-shaped alumina particles require a bias in the direction of crystal growth during the production process. In contrast, the plate-like alumina particles satisfying the longitudinal relaxation time T1 have a plate-like shape but are highly crystalline, and therefore have the advantages of plate-like alumina particles, such as excellent thermal conductivity, while also improving the shape retention and processing stability of the resin composition, making them extremely useful.

[0045] The pH of the isoelectric point of the plate-like alumina particles is, for example, in the range of 2 to 6, preferably in the range of 2.5 to 5, and more preferably in the range of 3 to 4. The plate-like alumina particles having an isoelectric point within the above range have a high electrostatic repulsive force, and can enhance the dispersion stability when blended into the above-mentioned dispersion medium, and can be easily modified by surface treatment such as a coupling treatment agent for further improving performance.

[0046] The pH value of the isoelectric point is obtained by measuring the zeta potential with a zeta potential measuring device (Malvern Instruments, Zetasizer Nano ZSP) by stirring 20 mg of sample and 10 mL of 10 mM KCl aqueous solution for 3 minutes in stirring / degassing mode with a foam remover (Thinky Corporation, ARE-310), leaving it to stand for 5 minutes, and using the supernatant as the measurement sample. 0.1 N HCl is added to the sample with an automatic titration device, and the zeta potential is measured in the range up to pH = 2 (applied voltage 100 V, Monomodl mode), and the pH at the isoelectric point where the potential becomes zero is evaluated.

[0047] The plate-shaped alumina particles have a density of, for example, 3.70 g / cm 3 More than 4.10g / cm 3 and the density is 3.72 g / cm 3 More than 4.10g / cm 3 It is preferable that the density is 3.80 g / cm or less. 3 More than 4.10g / cm 3 It is more preferable that: The density can be measured using a dry automatic density meter (Micromeritics, Accupic II1330) at a measurement temperature of 25°C and helium as the carrier gas after pretreatment of the plate-like alumina particles at 300°C for 3 hours.

[0048] [alumina] The "alumina" contained in the plate-like alumina particles is aluminum oxide, and may be transition alumina of various crystal forms such as γ, δ, θ, κ, etc., or may contain alumina hydrate in the transition alumina, but is basically preferably in the α crystal form (α type) in terms of superior mechanical strength or thermal conductivity. The α crystal form is a dense crystal structure of alumina, and is advantageous in improving the mechanical strength or thermal conductivity of the plate-like alumina. The α-crystallinity ratio is preferably as close to 100% as possible, since the inherent properties of the α-crystal form are more easily exhibited. The α-crystallinity ratio of the plate-like alumina particles is, for example, 90% or more, preferably 95% or more, and more preferably 99% or more.

[0049] [Silicon-Germanium] The platelet alumina particles of this embodiment may contain silicon and / or germanium. The silicon or germanium may be derived from silicon, a silicon compound, and / or a germanium compound that can be used as a shape control agent. By utilizing these, it is possible to produce plate-like alumina particles having excellent luster in the production method described below.

[0050] (silicon) The plate-like alumina particles according to the present embodiment may contain silicon. The plate-like alumina particles according to the present embodiment may contain silicon in the surface layer. Here, the "surface layer" refers to a region within 10 nm from the surface of the plate-like alumina particle according to the present embodiment. This distance corresponds to the detection depth of the XPS used for the measurements in the examples.

[0051] The plate-like alumina particles may have silicon unevenly distributed in the surface layer. Here, "distributed unevenly in the surface layer" refers to a state in which the mass of silicon per unit volume in the surface layer is greater than the mass of silicon per unit volume in the rest of the surface layer. The fact that silicon is unevenly distributed in the surface layer can be determined by comparing the results of surface analysis by XPS and overall analysis by XRF.

[0052] The silicon contained in the plate-like alumina particles may be silicon alone or silicon in a silicon compound. The plate-like alumina particles may contain at least one selected from the group consisting of mullite, Si, SiO2, SiO, and aluminum silicate produced by reacting with alumina as silicon or a silicon compound, and may contain the above-mentioned substance in the surface layer. Mullite will be described later.

[0053] When silicon or a silicon compound containing silicon is used as a shape control agent, the plate-like alumina particles can detect Si by XRF analysis. The molar ratio of Si to Al of the plate-like alumina particles, [Si] / [Al], obtained by XRF analysis, is, for example, 0.04 or less, preferably 0.035 or less, and more preferably 0.02 or less. Furthermore, the value of the molar ratio [Si] / [Al] is not particularly limited, but is, for example, 0.003 or more, preferably 0.004 or more, and more preferably 0.005 or more. The molar ratio of Si to Al, [Si] / [Al], of the plate-like alumina particles obtained by XRF analysis is, for example, 0.003 or more and 0.04 or less, preferably 0.004 or more and 0.035 or less, and more preferably 0.005 or more and 0.02 or less. The plate-like alumina particles having the molar ratio [Si] / [Al] within the above range obtained by the XRF analysis satisfy the above (006 / 113) ratio value, have better luster, and have a good plate-like shape. In addition, deposits are less likely to adhere to the surface of the plate-like alumina particles, and the quality is excellent. The deposits are considered to be SiO2 particles, and are considered to be generated due to excess Si when the generation of mullite on the surface layer of the plate-like alumina particles becomes saturated. When using plate-like alumina particles having a larger particle size, the molar ratio of Si to Al, [Si] / [Al], obtained by XRF analysis, of the plate-like alumina particles is preferably 0.0003 or more and 0.01 or less, preferably 0.0005 or more and 0.0025 or less, and more preferably 0.0006 or more and 0.001 or less.

[0054] The plate-like alumina particles may contain silicon corresponding to the silicon or silicon compound containing silicon used in the production method thereof. The silicon content relative to 100 mass% of the plate-like alumina particles, calculated as silicon dioxide, is preferably 10 mass% or less, more preferably 0.001 to 5 mass%, further preferably 0.01 to 4 mass%, further preferably 0.3 to 2.5 mass%, and particularly preferably 0.6 to 2.5 mass%. When using plate-like alumina particles having a larger particle size, the silicon content relative to 100 mass% of the plate-like alumina particles, calculated as silicon dioxide, is preferably 10 mass% or less, more preferably 0.001 to 3 mass%, even more preferably 0.01 to 1 mass%, and particularly preferably 0.03 to 0.3 mass%.

[0055] (Mullite) The plate-like alumina particles of the embodiment may contain mullite. It is presumed that the inclusion of mullite in the surface layer of the plate-like alumina particles improves the selectivity of the molybdenum compound constituting the inorganic coating portion, and allows the inorganic coating portion to be efficiently formed on the plate-like alumina particles. Mullite, when contained in the surface layer of plate-shaped alumina particles, significantly reduces the wear of equipment. Mullite, which may be contained in the surface layer of plate-shaped alumina particles, is a composite oxide of Al and Si. X S Y O z However, there is no particular limit to the values ​​of x, y, and z. A more preferable range is Al2Si1O5 to Al6Si2O 13 In the examples described later, the XRD peak intensity is confirmed for Al. 2.85 SiO 6.3 , Al3SiO 6.5 , Al 3.67 SiO 7.5 , Al4Si1O8, or Al6Si2O 13 The plate-shaped alumina particles contain Al 2.85 SiO 6.3 , Al3SiO 6.5 , Al 3.67SiO 7.5 , Al4Si1O8, and Al6Si2O 13 The surface layer may contain at least one compound selected from the group consisting of: Here, the "surface layer" refers to a region within 10 nm from the surface of the plate-like alumina particle. This distance corresponds to the detection depth of the XPS used in the measurements in the examples. The plate-like alumina particles preferably have mullite unevenly distributed in the surface layer. Here, "distributed unevenly in the surface layer" refers to a state in which the mass of mullite per unit volume in the surface layer is greater than the mass of mullite per unit volume in the other parts of the surface layer. The uneven distribution of mullite in the surface layer can be determined by comparing the results of surface analysis by XPS and overall analysis by XRF, as shown in the examples described later.

[0056] The mullite of the surface layer may form a mullite layer, or may be a mixture of mullite and alumina. The interface between the mullite and alumina of the surface layer may be in a state where the mullite and alumina are in physical contact with each other, or the mullite and alumina may form a chemical bond such as Si-O-Al.

[0057] (germanium) The plate-like alumina particles according to the embodiment may contain germanium. Also, the plate-like alumina particles may contain germanium in a surface layer. Although it depends on the raw material used, the plate-shaped alumina particles are germanium or germanium compounds such as Ge, GeO2, GeO, GeCl2, GeBr4, GeI4, GeS2, AlGe, GeTe, GeTe 3、 It may contain at least one selected from the group consisting of compounds such as As2, GeSe, GeS3As, SiGe, Li2Ge, FeGe, SrGe, GaGe, and oxides thereof, and the above substance may be contained in the surface layer. In addition, the "germanium or germanium compound" contained in the plate-like alumina particles and the "raw germanium compound" used as the shape control agent of the raw material may be the same type of germanium compound. For example, GeO2 may be detected in the plate-like alumina particles produced by adding GeO2 to the raw material.

[0058] When germanium or a germanium compound is contained in the surface layer of the plate-like alumina particles, a significant reduction in wear of the equipment is achieved. Here, the "surface layer" refers to the area within 10 nm from the surface of the plate-like alumina particles. The plate-like alumina particles preferably have germanium or a germanium compound unevenly distributed in the surface layer. Here, "distributed unevenly in the surface layer" refers to a state in which the mass of germanium or a germanium compound per unit volume in the surface layer is greater than the mass of germanium or a germanium compound per unit volume in the other part of the surface layer. The uneven distribution of germanium or a germanium compound in the surface layer can be determined by comparing the results of a surface analysis by XPS and a total analysis by XRF.

[0059] The plate-like alumina particles contain germanium corresponding to the raw germanium compound used in the production method. The germanium content relative to 100% by mass of the plate-like alumina particles is preferably 10% by mass or less, more preferably 0.001-5% by mass, even more preferably 0.01-4% by mass, and particularly preferably 0.1-3.0% by mass, calculated as germanium dioxide. The germanium content can be determined by XRF analysis. The XRF analysis should be carried out under the same measurement conditions as those described in the Examples below, or under compatible conditions that give the same measurement results.

[0060] The germanium or germanium compound of the surface layer may form a layer, or may be in a state where germanium or germanium compound and alumina are mixed. The interface between the germanium or germanium compound of the surface layer and alumina may be in a state where the germanium or germanium compound and alumina are in physical contact with each other, or the germanium or germanium compound and alumina may form a chemical bond such as Ge-O-Al.

[0061] [molybdenum] The plate-like alumina particles of this embodiment contain molybdenum. In addition, the plate-like alumina particles preferably contain molybdenum in their surface layers. This is believed to improve the selectivity of the molybdenum compound that constitutes the inorganic coating portion, and to allow the inorganic coating portion to be efficiently formed on the plate-like alumina particles.

[0062] The molybdenum may be derived from a molybdenum compound used as a fluxing agent in the method for producing alumina particles described below.

[0063] By utilizing molybdenum, it is possible to produce plate-like alumina particles that are highly crystalline despite their plate-like shape and have a high aspect ratio, in a production method described below.

[0064] By increasing the amount of molybdenum used, it is possible to obtain plate-like alumina particles having an appropriate particle size and containing molybdenum on the alumina surface layer, and it is also advantageous to form an inorganic coating portion on the surface of the obtained plate-like alumina particles. Furthermore, by utilizing molybdenum, the formation of mullite is promoted, and plate-like alumina particles having a high aspect ratio and excellent dispersibility can be produced. In addition, by utilizing the properties of molybdenum contained in the plate-like alumina particles, it may be possible to apply them to applications such as oxidation reaction catalysts and optical materials.

[0065] The molybdenum is not particularly limited, and in addition to molybdenum metal, it includes molybdenum oxide, partially reduced molybdenum compounds, molybdates, etc. The molybdenum may be contained in the plate-like alumina particles in any of the polymorphs that the molybdenum compound can take, or in combination, and may be contained in the plate-like alumina particles as α-MoO3, β-MoO3, MoO2, MoO, a molybdenum cluster structure, etc.

[0066] The form in which molybdenum is contained is not particularly limited, and may be contained in a form in which it is adhered to the surface of the plate-like alumina particles, or may be contained in a form in which it is substituted for part of the aluminum in the crystal structure of the alumina, or may be a combination of these.

[0067] In this embodiment, the ratio of the amount of MoO3 to the amount of Al2O3 in the plate-like alumina particles ([MoO3] / [Al2O3]×100) obtained by X-ray fluorescence (XRF) analysis XRF is preferably 1 or more. ([MoO3] / [Al2O3]×100) XRF is more preferably 10 or more, further preferably 15 or more, and particularly preferably 20 or more. ([MoO3] / [Al2O3]×100) XRF is, for example, the ratio of the content of Al2O3 relative to 100% by mass of the plate-like alumina particles to the content of MoO3 relative to 100% by mass of the plate-like alumina particles. This makes it possible to improve the brilliance of the alumina particles while enhancing the oxidation catalytic function of molybdenum oxide.

[0068] The molybdenum content relative to 100% by mass of the plate-like alumina particles obtained by XRF analysis is preferably 1% by mass or less in terms of molybdenum trioxide, and by adjusting the firing temperature, firing time, and sublimation rate of the molybdenum compound, it is more preferably 0.001 to 1% by mass, further preferably 0.01 to 0.9% by mass, and particularly preferably 0.1 to 0.8% by mass. A molybdenum content of 1% by mass or less is preferable because it improves the α single crystal quality of the alumina.

[0069] [potassium] The plate-like alumina particles may further contain potassium.

[0070] The potassium may be derived from potassium that can be used as a fluxing agent in the method for producing alumina particles described below. By utilizing potassium, the particle size of the alumina particles can be appropriately increased in the method for producing alumina particles described below.

[0071] The potassium is not particularly limited, but includes potassium metal, potassium oxide, partially reduced potassium compounds, and the like.

[0072] The form in which potassium is contained is not particularly limited, and may be contained in a form in which potassium is attached to the surface of the tabular alumina of the tabular alumina particles, or may be contained in a form in which potassium is substituted for part of the aluminum in the crystal structure of the alumina, or may be a combination of these.

[0073] The potassium content relative to 100% by mass of the alumina particles, calculated as potassium oxide (KO) by XRF analysis, is preferably 0.01% by mass or more, more preferably 0.01 to 1.0% by mass, even more preferably 0.03 to 0.5% by mass, and particularly preferably 0.05 to 0.3% by mass. Alumina particles having a potassium content within the above range are preferred because they have a polyhedral shape and have suitable values ​​such as an average particle size.

[0074] (other atoms) The other atoms refer to those that are intentionally added to the alumina particles for the purpose of imparting mechanical strength or electrical or magnetic functions, within the scope of not impairing the effects of the present invention.

[0075] The other atoms are not particularly limited, but include zinc, manganese, calcium, strontium, yttrium, etc. These other atoms may be used alone or in combination of two or more.

[0076] The content of other atoms in the alumina particles is preferably 5 mass % or less, and more preferably 2 mass % or less, based on the mass of the alumina particles.

[0077] [Inevitable impurities] The alumina particles may contain unavoidable impurities.

[0078] Inevitable impurities are impurities that originate from metal compounds used in production, are present in raw materials, or are inevitably mixed into alumina particles during the production process. Although they are not actually required, they are present in trace amounts and do not affect the properties of the alumina particles.

[0079] The inevitable impurities are not particularly limited, but include magnesium, calcium, strontium, barium, scandium, yttrium, lanthanum, cerium, sodium, etc. These inevitable impurities may be contained alone or in combination of two or more kinds.

[0080] The content of unavoidable impurities in the alumina particles is preferably 10,000 ppm or less, more preferably 1,000 ppm or less, and further preferably 10 to 500 ppm, based on the mass of the alumina particles.

[0081] <Inorganic coating part> The inorganic coating portion coats at least a portion of the surface of the alumina particle, and is preferably constituted by an inorganic coating layer coating at least a portion of the surface of the alumina particle. As described above, the inorganic coating portion is provided on the surface of the alumina particle. "On the surface of the alumina particle" means the outside of the surface of the alumina particle. Therefore, the inorganic coating portion formed on the outside of the surface of the alumina particle is clearly distinguished from the surface layer containing mullite or germanium formed on the inside of the surface of the alumina particle.

[0082] The inorganic coating portion is made of molybdenum oxide, such as MoO3, MoO2, and MoOx (x=2 to 3).

[0083] The shape of the molybdenum oxide constituting the inorganic coating portion is not particularly limited, and may be, for example, particulate, such as spherical, needle-like, polyhedral, disc-like, hollow, or porous. The average particle size of the particulate molybdenum compound is, for example, preferably 1 nm or more and 500 nm or less, and more preferably 5 nm or more and 200 nm or less. The molybdenum oxide may be crystalline or amorphous.

[0084] When the inorganic coating portion is an inorganic coating layer, the thickness of one layer of the inorganic coating layer formed on the surface of the alumina particle is preferably 0.1 nm or more and 100 nm or less, preferably 1 nm or more and 50 nm or less, and particularly preferably 3 nm or more and 20 nm or less.

[0085] In the composite particle having the inorganic coating portion, the ratio of the amount of MoO3 to the amount of Al2O3 on the surface of the plate-like alumina particle obtained by X-ray photoelectron spectroscopy (XPS) analysis ([MoO3] / [Al2O3]×100) XPS is 15 or more. ([MoO3] / [Al2O3]×100) XPS is, for example, the ratio of the Al2O3 content relative to 100% by mass of the plate-like alumina particles to the MoO3 content relative to 100% by mass of the plate-like alumina particles. ([MoO3] / [Al2O3]×100) XPS When the ratio is 15 or more, the molybdenum oxide is unevenly distributed on the surface of the composite particle, and various properties such as antibacterial and antiviral functions due to the molybdenum oxide can be efficiently and sufficiently exhibited.

[0086] In order to further improve the above properties, ([MoO3] / [Al2O3]×100) XPS is preferably 20 or more, more preferably 25 or more, and even more preferably 30 or more.

[0087] In the composite particle of this embodiment, it is preferable that molybdenum oxide is unevenly distributed on the surface of the alumina particle. Here, "distributed unevenly on the surface" refers to a state in which the mass of molybdenum oxide per unit volume on the surface is greater than the mass of molybdenum oxide per unit volume other than the surface. The uneven distribution of molybdenum oxide on the surface can be determined by comparing the results of surface analysis by XPS and overall analysis by XRF.

[0088] For example, (1) the ratio of the amount of MoO3 to the amount of Al2O3 on the surface of a plate-shaped alumina particle obtained by X-ray photoelectron spectroscopy (XPS) analysis ([MoO3] / [Al2O3]×100) XPS (2) the ratio of the amount of MoO3 to the amount of Al2O3 in the plate-shaped alumina particles obtained by X-ray fluorescence (XRF) analysis ([MoO3] / [Al2O3]×100) XRF is 1 or more, and (3) ([MoO3] / [Al2O3]×100) XPS ([MoO3] / [Al2O3]×100) XRF This allows the molybdenum oxide to fully exhibit various properties such as antibacterial properties, antiviral properties, and oxidation catalyst properties.

[0089] [Organic compound layer on the surface of composite particles] In one embodiment, the composite particles may have an organic compound layer on their surface. The organic compound constituting the organic compound layer is present on the surface of the composite particles and has the function of adjusting the surface properties of the composite particles. For example, composite particles having an organic compound on their surface improve the affinity with resin, and therefore the function of the composite particles as a filler can be maximized.

[0090] Organic compounds include, but are not limited to, organosilanes, alkylphosphonic acids, and polymers.

[0091] Examples of the organic silane include alkyltrimethoxysilanes or alkyltrichlorosilanes having an alkyl group having 1 to 22 carbon atoms, such as methyltrimethoxysilane, dimethyldimethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, isopropyltrimethoxysilane, isopropyltriethoxysilane, pentyltrimethoxysilane, and hexyltrimethoxysilane; 3,3,3-trifluoropropyltrimethoxysilane, tridecafluoro-1,1,2,2-tetrahydrooctyl)trichlorosilanes; phenyltrimethoxysilane, phenyltriethoxysilane, p-chloromethylphenyltrimethoxysilane, and p-chloromethylphenyltriethoxysilanes.

[0092] Examples of the phosphonic acid include methylphosphonic acid, ethylphosphonic acid, propylphosphonic acid, butylphosphonic acid, pentylphosphonic acid, hexylphosphonic acid, heptylphosphonic acid, octylphosphonic acid, decylphosphonic acid, dodecylphosphonic acid, octadecylphosphonic acid, 2-ethylhexylphosphonic acid, cyclohexylmethylphosphonic acid, cyclohexylethylphosphonic acid, benzylphosphonic acid, phenylphosphonic acid, and dodecylbenzenephosphonic acid.

[0093] As the polymer, for example, poly(meth)acrylates can be suitably used.Specific examples include polymethyl(meth)acrylate, polyethyl(meth)acrylate, polybutyl(meth)acrylate, polybenzyl(meth)acrylate, polycyclohexyl(meth)acrylate, polyt-butyl(meth)acrylate, polyglycidyl(meth)acrylate, polypentafluoropropyl(meth)acrylate, etc., and also include general-purpose polymers such as polystyrene, polyvinyl chloride, polyvinyl acetate, epoxy resin, polyester, polyimide, polycarbonate, etc.

[0094] The organic compound may be contained alone or in combination of two or more kinds.

[0095] The form in which the organic compound is contained is not particularly limited, and the organic compound may be bonded to the alumina by a covalent bond, or may be coated with the alumina or the material of the inorganic coating portion.

[0096] The content of the organic compound is preferably 20% by mass or less, more preferably 10% by mass or more and 0.01% by mass or less, based on the mass of the alumina particles. When the content of the organic compound is 20% by mass or less, it is preferable because the physical properties derived from the composite particles can be easily expressed.

[0097] In the composite particles configured as described above, the pH of the dispersion (0.1 mass%) in which the composite particles are dispersed in water is preferably less than 5.0, more preferably 4.5 or less. When the pH of the aqueous dispersion is less than 5.0, the antibacterial activity and antiviral activity can be further improved.

[0098] <Method of manufacturing composite particles> Next, the method for producing the composite particles according to the present embodiment will be illustrated in detail, but the method for producing the composite particles according to the present embodiment is not limited to the method for producing the composite particles described below.

[0099] The method for producing composite particles according to the present embodiment includes the steps of producing alumina particles by firing a first mixture containing an aluminum compound containing an aluminum element, a molybdenum compound containing a molybdenum element, and a shape control agent for controlling the shape of the alumina particles, and firing a second mixture containing the alumina particles and a molybdenum compound containing a molybdenum element to form an inorganic coating portion composed of molybdenum oxide on the surface of the alumina particles. Hereinafter, as an example of the method for producing composite particles according to the present embodiment, a method for producing composite particles using plate-like alumina particles will be described.

[0100] <Method of manufacturing plate-like alumina particles> The method for producing the plate-like alumina particles that constitute the composite particles is not particularly limited, and known techniques can be applied as appropriate. From the viewpoint of being able to suitably control alumina having a high α crystallization rate at a relatively low temperature, a production method using a flux method that utilizes a molybdenum compound can be preferably applied.

[0101] More specifically, a preferred method for producing plate-like alumina particles includes a step of calcining an aluminum compound in the presence of a molybdenum compound and a shape control agent (calcination step). The calcination step may be a step of calcining a mixture obtained in a step of obtaining a mixture to be calcined (mixing step).

[0102] [Mixing process] The mixing step is a step of mixing an aluminum compound, a molybdenum compound, and a shape control agent to obtain a first mixture. The first mixture preferably further contains a potassium compound. The contents of the first mixture will be described below.

[0103] (Aluminum Compounds) The aluminum compound is a raw material for the plate-like alumina particles of this embodiment, and is not particularly limited as long as it becomes alumina by heat treatment. For example, aluminum chloride, aluminum sulfate, basic aluminum acetate, aluminum hydroxide, boehmite, pseudo-boehmite, transition alumina (γ-alumina, δ-alumina, θ-alumina, etc.), α-alumina, mixed alumina having two or more crystal phases, etc. can be used, and the physical form, such as the shape, particle size, and specific surface area, of these aluminum compounds as precursors is not particularly limited.

[0104] According to the flux method described in detail below, the aluminum compound can be suitably used regardless of its shape, for example, spherical, amorphous, oriented structure (wire, fiber, ribbon, tube, etc.), sheet, etc.

[0105] Similarly, the particle size of the aluminum compound may be from several nm to several hundred μm in the case of the flux method described in detail below.

[0106] The specific surface area of ​​the aluminum compound is not particularly limited. Since the molybdenum compound acts effectively, the larger the specific surface area, the more preferable it is. However, by adjusting the firing conditions and the amount of the molybdenum compound used, any specific surface area can be used as the raw material.

[0107] The aluminum compound may be composed of only the aluminum compound, or may be a complex of the aluminum compound and an organic compound. For example, an organic / inorganic complex obtained by modifying an aluminum compound with an organic silane, or an aluminum compound complex adsorbed with a polymer, may be suitably used. When using these complexes, the content of the organic compound is not particularly limited, but from the viewpoint of efficiently producing plate-like alumina particles, the content is preferably 60% by mass or less, more preferably 30% by mass or less.

[0108] (shape control agent) To form the plate-like alumina particles according to the embodiment, a shape control agent can be used, which plays an important role in the growth of plate-like crystals of alumina by calcining an alumina compound in the presence of a molybdenum compound.

[0109] The state in which the shape control agent is present is not particularly limited, and for example, a physical mixture of the shape control agent and the aluminum compound, or a complex in which the shape control agent is present uniformly or locally on the surface or inside of the aluminum compound, can be suitably used.

[0110] The shape control agent may be added to the aluminum compound, or may be contained in the aluminum compound as an impurity.

[0111] The shape control agent plays an important role in the growth of plate-like crystals. In the molybdenum oxide flux method, molybdenum oxide reacts with an aluminum compound to form aluminum molybdate, and then the change in chemical potential during the decomposition of this aluminum molybdate serves as the driving force for crystallization, forming hexagonal bipyramidal polyhedral particles with well-developed idiomorphic faces (113). In the manufacturing method of the embodiment, the shape control agent is localized near the particle surface during the α-alumina growth process, significantly inhibiting the growth of the idiomorphic faces (113), which results in relatively fast growth of the crystal orientation in the face direction, and the (001) or (006) face grows, forming a plate-like shape. By using a molybdenum compound as a flux agent, it is possible to more easily form molybdenum-containing plate-like alumina particles with a high α-crystallization rate.

[0112] It should be noted that the above mechanism is merely speculation, and even if the effects of the present invention are obtained through a mechanism different from the above mechanism, this is still within the technical scope of the present invention.

[0113] As for the type of shape control agent, it is preferable to use at least one selected from the group consisting of silicon, silicon compounds, and germanium compounds, from the viewpoint of being able to produce plate-like alumina particles with a higher aspect ratio, better dispersibility, and better productivity. Silicon or silicon compounds and germanium compounds can be used in combination. From the viewpoint of being a source of Si for mullite and being able to efficiently produce mullite, it is preferable to use silicon or silicon compounds containing silicon as the shape control agent. In addition, it is preferable to use germanium compounds as the shape control agent, from the viewpoint of being able to produce plate-like alumina particles with a higher aspect ratio and a larger particle size than when silicon or silicon compounds are used. By the above-mentioned flux method using silicon or a silicon compound as the shape control agent, plate-like alumina particles containing mullite on the surface layer can be easily produced. By the above-mentioned flux method using a raw germanium compound as a shape control agent, plate-like alumina particles containing germanium or a germanium compound can be easily produced.

[0114] Silicon or silicon compounds Silicon or silicon compounds containing silicon element are not particularly limited, and known compounds can be used. Specific examples of silicon or silicon compounds containing silicon element include artificially synthesized silicon compounds such as metal silicon, organosilane, silicon resin, silica fine particles, silica gel, mesoporous silica, SiC, and mullite; and natural silicon compounds such as biosilica. Among these, organosilane, silicon resin, and silica fine particles are preferably used from the viewpoint of forming a more uniform composite or mixture with an aluminum compound. The silicon compounds containing silicon or silicon element may be used alone or in combination of two or more kinds. In addition, they may be used in combination with other shape control agents as long as the effect of the present invention is not impaired.

[0115] The shape of silicon or a silicon compound containing elemental silicon is not particularly limited, and for example, a sphere, an amorphous shape, an aspected structure (wire, fiber, ribbon, tube, etc.), a sheet, etc. can be suitably used.

[0116] Germanium compounds The raw germanium compound used as the shape control agent is not particularly limited, and known compounds can be used. Specific examples of the raw germanium compound include germanium metal, germanium dioxide, germanium monoxide, germanium tetrachloride, and organic germanium compounds having Ge-C bonds. The raw germanium compound may be used alone or in combination of two or more. In addition, it may be used in combination with other shape control agents as long as it does not impair the effects of the present invention.

[0117] The shape of the raw material germanium compound is not particularly limited, and for example, a sphere, an amorphous shape, an aspected structure (wire, fiber, ribbon, tube, etc.), a sheet, etc. can be suitably used.

[0118] (Molybdenum Compounds) The molybdenum compound provides a fluxing function for the alpha crystal growth of alumina at relatively low temperatures, as will be described below. The molybdenum compound is not particularly limited, but may be, for example, molybdenum oxide, an acid radical anion (MoO x n- ) and compounds containing the same.

[0119] The acid radical anion (MoO x n- ) is not particularly limited, but may be, for example, molybdic acid, sodium molybdate, potassium molybdate, lithium molybdate, HPMo 12 O 40 , H3SiMo 12 O 40 , NH4Mo7O 12 , molybdenum disulfide, etc.

[0120] The molybdenum compound may contain silicon, in which case the molybdenum compound containing silicon serves as both a flux agent and a shape control agent.

[0121] Among the above molybdenum compounds, it is preferable to use molybdenum oxide, which is easy to sublimate and is cost-effective. The above molybdenum compounds may be used alone or in combination of two or more kinds.

[0122] In addition, potassium molybdate (K2Mo n O 3n+1(n=1 to 3) contains potassium and therefore may also function as a potassium compound, which will be described later. In the manufacturing method of the embodiment, using potassium molybdate as a fluxing agent is synonymous with using a molybdenum compound and a potassium compound as fluxing agents.

[0123] (Potassium compounds) A potassium compound may be further used in combination with the shape control agent. The potassium compound is not particularly limited, but includes potassium chloride, potassium chlorite, potassium chlorate, potassium sulfate, potassium hydrogen sulfate, potassium sulfite, potassium hydrogen sulfite, potassium nitrate, potassium carbonate, potassium hydrogen carbonate, potassium acetate, potassium oxide, potassium bromide, potassium bromate, potassium hydroxide, potassium silicate, potassium phosphate, potassium hydrogen phosphate, potassium sulfide, potassium hydrogen sulfide, potassium molybdate, potassium tungstate, etc. In this case, the potassium compound includes isomers, as in the case of molybdenum compounds. Among these, it is preferable to use potassium carbonate, potassium hydrogen carbonate, potassium oxide, potassium hydroxide, potassium chloride, potassium sulfate, and potassium molybdate, and it is more preferable to use potassium carbonate, potassium hydrogen carbonate, potassium chloride, potassium sulfate, and potassium molybdate.

[0124] The above potassium compounds may be used alone or in combination of two or more kinds.

[0125] The potassium compound contributes to efficient formation of mullite on the alumina surface layer, and also contributes to efficient formation of a germanium-containing layer on the alumina surface layer.

[0126] It is also preferable to use a potassium compound together with a molybdenum compound as a fluxing agent.

[0127] Among the above, potassium molybdate contains molybdenum, and therefore can also function as the molybdenum compound described above. When potassium molybdate is used as a fluxing agent, it can exert the same effect as when a molybdenum compound and a potassium compound are used as fluxing agents.

[0128] As the potassium compound used when the raw materials are charged or generated in a reaction during the temperature rise process during calcination, a water-soluble potassium compound, for example, potassium molybdate, does not vaporize even in the calcination temperature range and can be easily recovered by washing after calcination. This reduces the amount of molybdenum compounds released outside the calcination furnace, and also enables a significant reduction in production costs.

[0129] When a molybdenum compound and a potassium compound are used as a fluxing agent, the molar ratio of the molybdenum element of the molybdenum compound to the potassium element of the potassium compound (molybdenum element / potassium element) is preferably 5 or less, more preferably 0.01 to 3, and even more preferably 0.5 to 1.5, since this can further reduce production costs. When the molar ratio (molybdenum element / potassium element) is within the above range, this is preferable because plate-like alumina particles having a large particle size can be obtained. (metal compound) The metal compound can have a function of promoting the crystal growth of alumina, as described below. The metal compound can be used during firing as desired. Note that since the metal compound has a function of promoting the crystal growth of α-alumina, it is not essential for the production of the plate-like alumina particles according to the present invention.

[0130] The metal compound is not particularly limited, but preferably contains at least one selected from the group consisting of Group II metal compounds and Group III metal compounds.

[0131] Examples of the Group II metal compound include magnesium compounds, calcium compounds, strontium compounds, and barium compounds.

[0132] Examples of the Group III metal compound include a scandium compound, an yttrium compound, a lanthanum compound, and a cerium compound.

[0133] The above-mentioned metal compounds refer to oxides, hydroxides, carbonates, and chlorides of metal elements. For example, yttrium compounds include yttrium oxide (Y2O3), yttrium hydroxide, and yttrium carbonate. Of these, the metal compounds are preferably oxides of metal elements. These metal compounds include isomers.

[0134] Among these, the metal compounds of the third periodic elements, the metal compounds of the fourth periodic elements, the metal compounds of the fifth periodic elements, and the metal compounds of the sixth periodic elements are preferred, the metal compounds of the fourth periodic elements and the metal compounds of the fifth periodic elements are more preferred, and the metal compounds of the fifth periodic elements are even more preferred. Specifically, it is preferred to use magnesium compounds, calcium compounds, yttrium compounds, and lanthanum compounds, it is more preferred to use magnesium compounds, calcium compounds, and yttrium compounds, and it is particularly preferred to use yttrium compounds.

[0135] The addition rate of the metal compound is preferably 0.02 to 20 mass% based on the mass equivalent value of aluminum atoms in the aluminum compound, and more preferably 0.1 to 20 mass%. When the addition rate of the metal compound is 0.02 mass% or more, the crystal growth of α-alumina containing molybdenum can proceed favorably, which is preferable. On the other hand, when the addition rate of the metal compound is 20 mass% or less, it is preferable that plate-like alumina particles having a low content of impurities derived from the metal compound can be obtained.

[0136] [yttrium] When an aluminum compound is calcined in the presence of an yttrium compound as a metal compound, crystal growth proceeds more favorably in the calcination process, and α-alumina and a water-soluble yttrium compound are produced. At this time, the water-soluble yttrium compound is likely to be localized on the surface of the α-alumina, which is a plate-like alumina particle, so that if necessary, the yttrium compound can be removed from the plate-like alumina particle by washing with water, alkaline water, or a liquid obtained by heating these.

[0137] The amounts of the above-mentioned aluminum compound, molybdenum compound, silicon or silicon compound, germanium compound, potassium compound, etc. used are not particularly limited. For example, when the total amount of the raw materials calculated as oxide is taken as 100 mass %, the following first mixture is fired. 1) An aluminum compound having an aluminum content of preferably 50 mass% or more, more preferably 70 mass% or more and 99 mass% or less, and even more preferably 80 mass% or more and 94.5 mass% or less, calculated as Al2O3, A molybdenum compound that is preferably 40% by mass or less, more preferably 0.5% by mass or more and 20% by mass or less, and even more preferably 1% by mass or more and 7% by mass or less, calculated as MoO3, Silicon, a silicon compound, or a germanium compound, preferably 0.1% by mass or more and 10% by mass or less, in terms of SiO2 or GeO2, more preferably 0.5% by mass or more and less than 7% by mass of silicon, a silicon compound, or a germanium compound, and even more preferably 0.8% by mass or more and 4% by mass or less of silicon, a silicon compound, or a germanium compound, The first mixture was mixed with the above.

[0138] The silicon, silicon compound and / or germanium compound of the shape control agent may be silicon or a silicon compound, or may be a germanium compound. As the shape control agent, only silicon or a silicon compound may be used, only a germanium compound may be used, or only a combination of silicon or a silicon compound and a germanium compound may be used. When a germanium compound is used as the shape control agent, the first mixture may contain, when the total amount of the raw materials calculated as oxide is taken as 100 mass%, preferably 0.4 mass% or more and less than 1.5 mass%, and more preferably 0.7 mass% or more and 1.2 mass% or less of the germanium compound calculated as GeO2.

[0139] The above raw material blending (mass%) conditions may be freely combined for each raw material, and the lower and upper limits in each raw material blending (mass%) may also be freely combined.

[0140] When the first mixture further contains the potassium compound, the amount of the potassium compound used is not particularly limited, but when the total amount of the raw materials calculated as oxide is taken as 100 mass%, the potassium compound can be mixed in an amount of preferably 5 mass% or less, more preferably 0.01 mass% or more and 3 mass% or less, and even more preferably 0.05 mass% or more and 1 mass% or less, calculated as KO. It is believed that the potassium molybdate formed by the reaction with the molybdenum compound using the potassium compound has an effect of diffusing silicon and contributes to the promotion of the formation of mullite on the surface of the plate-like alumina particles. Similarly, it is believed that the use of a potassium compound causes potassium molybdate formed by reaction with a molybdenum compound to have an effect on the diffusion of the starting germanium, and contribute to promoting the formation of germanium or germanium compounds on the surface of the platelet alumina particles. As the potassium compound used when the raw materials are charged or generated in a reaction during the temperature rise process during calcination, a water-soluble potassium compound, for example, potassium molybdate, does not vaporize even in the calcination temperature range and can be easily recovered by washing after calcination. This reduces the amount of molybdenum compounds released outside the calcination furnace, and also enables a significant reduction in production costs.

[0141] In the flux method, it is also preferable to use a molybdenum compound and a potassium compound as fluxing agents. The compound containing molybdenum and potassium as a fluxing agent can be produced, for example, in the firing process using a molybdenum compound and a potassium compound, which are cheaper and easier to obtain, as raw materials. Here, the case where a molybdenum compound and a potassium compound are used as fluxing agents will be described as an example, combining the case where a molybdenum compound and a potassium compound are used as fluxing agents and the case where a compound containing molybdenum and potassium is used as fluxing agents.

[0142] The above-mentioned ranges of the amounts of the respective raw materials used can be appropriately combined as long as the total content does not exceed 100% by mass.

[0143] [Firing process] The calcination step is a step of calcining an aluminum compound in the presence of a molybdenum compound and a shape control agent, and may be a step of calcining the first mixture obtained in the mixing step.

[0144] The plate-like alumina particles can be obtained, for example, by calcining an aluminum compound in the presence of a molybdenum compound and a shape control agent. As described above, this production method is called the flux method.

[0145] The flux method is classified as a solution method. More specifically, the flux method is a crystal growth method that utilizes the fact that the crystal-flux two-component phase diagram shows a eutectic type. The mechanism of the flux method is presumed to be as follows. That is, when a mixture of a solute and flux is heated, the solute and flux become liquid phase. At this time, since the flux is a flux, in other words, since the solute-flux two-component phase diagram shows a eutectic type, the solute melts at a temperature lower than its melting point and forms a liquid phase. If the flux is evaporated in this state, the concentration of the flux decreases, in other words, the effect of the flux in lowering the melting point of the solute is reduced, and the evaporation of the flux becomes the driving force to cause crystal growth of the solute (flux evaporation method). The solute and flux can also cause crystal growth of the solute by cooling the liquid phase (slow cooling method).

[0146] The flux method has the advantages of being able to grow crystals at temperatures much lower than the melting point, being able to precisely control the crystal structure, and being able to form euhedral polyhedral crystals.

[0147] In the production of α-alumina particles by the flux method using a molybdenum compound as a flux, the mechanism is not necessarily clear, but it is presumed to be due to the following mechanism, for example. That is, when an aluminum compound is calcined in the presence of a molybdenum compound, aluminum molybdate is first formed. At this time, as can be understood from the above explanation, the aluminum molybdate grows α-alumina crystals at a temperature lower than the melting point of alumina. Then, for example, through the decomposition of aluminum molybdate and the evaporation of the flux, the crystal growth is accelerated, and alumina particles can be obtained. That is, the molybdenum compound functions as a flux, and α-alumina particles are produced via an intermediate called aluminum molybdate.

[0148] In the production of α-alumina particles by the flux method when a potassium compound is further used as a fluxing agent, the mechanism is not necessarily clear, but it is presumed to be due to the following mechanism, for example. First, a molybdenum compound reacts with an aluminum compound to form aluminum molybdate. Then, for example, aluminum molybdate decomposes to form molybdenum oxide and alumina, and at the same time, the molybdenum compound containing molybdenum oxide obtained by the decomposition reacts with a potassium compound to form potassium molybdate. The alumina crystals grow in the presence of the molybdenum compound containing potassium molybdate, and thus the plate-like alumina particles according to the embodiment can be obtained.

[0149] The method for firing the first mixture is not particularly limited, and can be any known or commonly used method.

[0150] In the step of producing the alumina particles, the first mixture is preferably fired at, for example, 900°C or higher. When the firing temperature exceeds 700°C, the aluminum compound reacts with the molybdenum compound to form aluminum molybdate. Furthermore, when the firing temperature reaches 900°C or higher, the aluminum molybdate decomposes and forms plate-like alumina particles due to the action of the shape control agent. In addition, in the plate-like alumina particles, it is believed that the aluminum molybdate decomposes to form alumina and molybdenum oxide, and the molybdenum compound is incorporated into the aluminum oxide particles. Furthermore, when the firing temperature is 900° C. or higher, it is believed that a molybdenum compound (eg, molybdenum trioxide) obtained by decomposition of aluminum molybdate reacts with a potassium compound to form potassium molybdate. Furthermore, when the firing temperature reaches 1000°C or higher, in the presence of molybdenum, the crystals of the platelet alumina particles grow and the Al2O3 and SiO2 on the surfaces of the platelet alumina particles react with each other, forming mullite with high efficiency. Similarly, when the firing temperature reaches 1000°C or higher, in the presence of molybdenum, the Al2O3 on the surface of the platelet alumina particles reacts with the Ge compounds as the crystals of the platelet alumina particles grow, resulting in the efficient formation of germanium dioxide and compounds having Ge-O-Al.

[0151] In addition, the state of the aluminum compound, the shape control agent, and the molybdenum compound during firing is not particularly limited, and it is sufficient that the molybdenum compound and the shape control agent are present in the same space where they can act on the aluminum compound. Specifically, they may be simply mixed by mixing the powders of the molybdenum compound, the shape control agent, and the aluminum compound, mechanically mixed using a grinder, or mixed using a mortar, or may be mixed in a dry or wet state.

[0152] The firing temperature conditions are not limited to the above, and are appropriately determined depending on the (006 / 113) ratio value, average particle size, aspect ratio, formation of mullite, the longitudinal relaxation time T1 value, dispersibility, etc. Usually, the firing temperature of the first mixture is preferably 900°C or higher, which is the decomposition temperature of aluminum molybdate (Al2(MoO4)3), more preferably 1000°C or higher, at which mullite or germanium compounds are formed with high efficiency, and more preferably 1200°C or higher, at which plate-like alumina particles with the longitudinal relaxation time T1 of 5 seconds or more (high crystallinity) can be easily obtained.

[0153] Generally, to control the shape of α-alumina obtained after firing, it is necessary to perform firing at high temperatures of over 2000°C, which is close to the melting point of α-alumina. However, there are significant challenges to be overcome in terms of the burden on the firing furnace and fuel costs in order to utilize this method industrially.

[0154] The manufacturing method of this embodiment can be carried out even at high temperatures exceeding 2000°C, but even at temperatures of 1600°C or less, which are significantly lower than the melting point of α-alumina, it is possible to form α-alumina that has a high α-crystallization rate and a high aspect ratio in a plate-like shape regardless of the shape of the precursor.

[0155] According to this embodiment, even under conditions where the maximum firing temperature is 900 to 1600°C, plate-like alumina particles having a high aspect ratio and an α-crystallization rate of 90% or more can be formed efficiently at low cost. It is more preferable to fire at a maximum temperature of 950 to 1500°C, even more preferable to fire at a maximum temperature in the range of 1000 to 1400°C, and most preferable to fire at a maximum temperature of 1200 to 1400°C.

[0156] Regarding the calcination time of the first mixture, it is preferable to raise the temperature to the predetermined maximum temperature in a range of 15 minutes to 10 hours, and to hold the calcination temperature for a period of 5 minutes to 30 hours. In order to efficiently form plate-like alumina particles, it is more preferable to hold the calcination temperature for about 10 minutes to 15 hours. By selecting conditions of a maximum temperature of 1000 to 1400°C and a firing holding time of 10 minutes to 15 hours, dense α-crystal polygonal plate-like alumina particles are easily obtained without aggregation. By selecting conditions of a maximum temperature of 1200 to 1400° C. and a firing holding time of 10 minutes to 15 hours, plate-like alumina particles having the longitudinal relaxation time T1 of 5 seconds or more (high crystallinity) can be easily obtained.

[0157] The firing atmosphere is not particularly limited as long as the effects of the present invention can be obtained. For example, an oxygen-containing atmosphere such as air or oxygen, or an inert atmosphere such as nitrogen, argon, or carbon dioxide is preferable, and an air atmosphere is more preferable in terms of cost.

[0158] The calcination apparatus is not necessarily limited, and a so-called calcination furnace can be used. The calcination furnace is preferably made of a material that does not react with the sublimated molybdenum oxide, and it is preferable to use a highly airtight calcination furnace so as to efficiently utilize the molybdenum oxide.

[0159] The alumina particles are preferably obtained by calcining an aluminum compound in the presence of a molybdenum compound and a shape-controlling agent, or in the presence of a molybdenum compound, a shape-controlling agent, a potassium compound and a metal oxide.

[0160] That is, a preferred method for producing alumina particles includes a step of calcining an aluminum compound in the presence of a molybdenum compound and a shape control agent, or in the presence of a molybdenum compound, a shape control agent, and a potassium compound (calcination step). The first mixture preferably further contains the above-mentioned metal compound. The metal compound is preferably a yttrium compound.

[0161] In the flux method using a molybdenum compound, molybdenum oxide reacts with an aluminum compound to form aluminum molybdate, and then the change in chemical potential during the decomposition of this aluminum molybdate is the driving force for crystallization, resulting in the formation of hexagonal bipyramidal polyhedral particles with well-developed idiomorphic faces (113). It is presumed that the shape control agent is localized near the particle surface during the α-alumina growth process, significantly inhibiting the growth of the idiomorphic faces (113), resulting in relatively fast growth of the crystal orientation in the face direction, and the (001) or (006) face growing, forming a plate-like morphology. Therefore, by using a molybdenum compound as a flux agent, it is possible to more easily form molybdenum-containing plate-like alumina particles with a high α-crystallization rate.

[0162] [Cooling process] When a molybdenum compound and a potassium compound are used as fluxing agents, the method for producing alumina particles may include a cooling step. The cooling step is a step of cooling the alumina crystal-grown in the firing step. More specifically, the cooling step may be a step of cooling a composition containing the alumina obtained by the firing step and the fluxing agent in a liquid phase.

[0163] The cooling rate is not particularly limited, but is preferably 1 to 1000°C / hour, more preferably 5 to 500°C / hour, and even more preferably 50 to 100°C / hour. A cooling rate of 1°C / hour or more is preferable because the manufacturing time can be shortened. On the other hand, a cooling rate of 1000°C / hour or less is preferable because the firing container is less likely to crack due to heat shock and can be used for a long time.

[0164] The cooling method is not particularly limited, and may be natural cooling or a cooling device may be used.

[0165] [Post-processing process] The method for producing plate-like alumina particles according to the embodiment may include a post-treatment step. The post-treatment step is a post-treatment step for the plate-like alumina particles, and is a step for removing a fluxing agent. The post-treatment step may be performed after the above-mentioned firing step, after the above-mentioned cooling step, or after the firing step and the cooling step. In addition, the post-treatment step may be repeated two or more times as necessary.

[0166] Post-treatment methods include washing and high temperature treatment, which may be performed in combination.

[0167] The washing method is not particularly limited, but the metal oxide can be removed by washing with water, an aqueous ammonia solution, an aqueous sodium hydroxide solution, or an acidic aqueous solution.

[0168] In this case, the molybdenum content can be controlled by appropriately changing the concentrations and amounts of water, ammonia aqueous solution, sodium hydroxide aqueous solution, and acidic aqueous solution used, as well as the cleaning locations and cleaning times.

[0169] As a method of high temperature treatment, a method of raising the temperature to the sublimation point or boiling point of the flux or higher can be mentioned.

[0170] [Crushing process] In the fired product, the plate-like alumina particles may aggregate and may not satisfy the particle size range suitable for the present invention. Therefore, the plate-like alumina particles may be pulverized as necessary to satisfy the particle size range suitable for the present invention. The method for pulverizing the fired product is not particularly limited, and any conventionally known pulverizing method such as a ball mill, a jaw crusher, a jet mill, a disk mill, a spectromill, a grinder, or a mixer mill can be used.

[0171] [Classification process] The plate-like alumina particles are preferably classified to adjust the average particle size, improve the powder flowability, or suppress the increase in viscosity when mixed with a binder to form a matrix. "Classification" refers to an operation of classifying particles into groups based on their size. The classification may be either wet or dry, but from the viewpoint of productivity, dry classification is preferred. Dry classification includes classification by sieving, as well as wind classification, which classifies based on the difference between centrifugal force and fluid drag, but from the viewpoint of classification accuracy, wind classification is preferred, and can be performed using a classifier such as an air classifier utilizing the Coanda effect, a swirling air classifier, a forced vortex centrifugal classifier, or a semi-free vortex centrifugal classifier. The above-mentioned pulverization step and classification step can be carried out at any stage required, including before or after the organic compound layer forming step described later. Depending on whether or not the pulverization or classification is carried out and the selection of the conditions therefor, for example, the average particle size of the obtained plate-like alumina particles can be adjusted.

[0172] The plate-like alumina particles of the embodiment or the plate-like alumina particles obtained by the manufacturing method of the embodiment are preferably those with little or no aggregation, because they easily exhibit their inherent properties, are more easily handled, and have better dispersibility when dispersed in a dispersion medium. In the manufacturing method of the plate-like alumina particles, if the above-mentioned pulverization step or classification step is not performed and the plate-like alumina particles with little or no aggregation are obtained, there is no need to perform the steps, and the plate-like alumina having the desired excellent properties can be manufactured with high productivity, which is preferable.

[0173] [Inorganic coating forming process] Next, an inorganic coating portion is formed on the surface of the plate-like alumina particles obtained above. In this embodiment, the second mixture containing the alumina particles and the molybdenum compound containing the molybdenum element is fired to form the inorganic coating portion composed of the molybdenum compound. The method for forming the inorganic coating portion is not particularly limited, but examples thereof include a gas phase method and a liquid phase method.

[0174] The molybdenum compound may be the same as the molybdenum compound mixed in the first mixture. For example, molybdenum oxide, an acid radical anion (MoO x n- ) is included.

[0175] The method of firing the second mixture is not particularly limited, and can be performed by a known and commonly used method. For example, it is preferable to fire the second mixture at 750°C or more and less than 1100°C. When the firing temperature is 750°C or more, firing can be performed at a temperature equal to or higher than the sublimation temperature of molybdenum oxide, and when the firing temperature is less than 1100°C, excessive sublimation of molybdenum oxide can be suppressed, and as a result, molybdenum oxide can be sufficiently attached to the surface of the alumina particles. From the viewpoint of the above effects, the firing temperature of the second mixture is more preferably 1100°C or less, and even more preferably 1000°C or less.

[0176] In the liquid phase method, for example, a dispersion liquid in which plate-like alumina particles are dispersed is prepared, and the pH of the dispersion liquid is adjusted and heated as necessary, and then an aqueous solution of a metal oxide such as molybdenum oxide is dropped into the dispersion liquid. At this time, it is preferable to maintain the pH constant with an alkaline aqueous solution. Thereafter, the dispersion liquid is stirred for a predetermined time, filtered, washed, and dried to obtain a powder. As a result, an inorganic coating portion composed of an oxide such as molybdenum oxide is formed on the surface of the plate-like alumina particles.

[0177] In this step, an inorganic coating layer may be formed so as to cover at least a portion of the surface of the plate-like alumina particles. In this case, for example, a layer is formed in a state where particles composed of a molybdenum compound are aggregated together.

[0178] [Organic compound layer formation process] In the present embodiment, the method for producing a composite particle may further include an organic compound layer forming step of forming an organic compound layer on the surface of the inorganic coating portion (also referred to as the composite particle surface) after the inorganic coating portion forming step. The organic compound layer forming step is usually performed after the baking step of the second mixture or after the post-treatment step.

[0179] The method for forming the organic compound layer is not particularly limited, and any known method can be appropriately adopted. For example, a method in which a liquid containing an organic compound is brought into contact with plate-like alumina particles containing molybdenum oxide, and then dried, can be mentioned.

[0180] An example of an organic compound that can be used to form an organic compound layer is an organic silane compound. The organic silane compound may be covalently bonded to at least a part or all of the silicon atoms and / or inorganic silicon compounds on the surface of the plate-like alumina particles through a reaction, and the alumina may be entirely or partially covered with the reactant. The method of providing the alumina surface may be attachment by immersion or chemical vapor deposition (CVD).

[0181] The amount of the organic silane compound used is preferably 20 mass% or less, more preferably 10 to 0.01 mass%, based on the mass of silicon atoms or inorganic silicon compounds contained on the surfaces of the plate-like alumina particles. When the amount of the organic silane compound used is 20 mass% or less, it is preferable because the physical properties derived from the alumina particles can be easily expressed.

[0182] The reaction between the alumina particles containing silicon atoms and / or inorganic silicon compounds and the organic silane compound can be carried out by a known and commonly used method for modifying the surface of a filler, and for example, a spraying method using a fluid nozzle, a dry method using stirring with shear force, a ball mill, a mixer, etc., or a wet method using a water-based or organic solvent-based system can be adopted. It is desirable to carry out the treatment using shear force to such an extent that the alumina particles used in the embodiment are not destroyed.

[0183] The system temperature in the dry method or the drying temperature after the treatment in the wet method is appropriately determined according to the type of the organosilane compound within a range in which the compound does not thermally decompose. For example, when treating with the above-mentioned organosilane compound, a temperature of 80 to 150°C is preferable.

[0184] <Resin composition> In one embodiment, a resin composition containing a resin and the composite particles of the embodiment is provided. The resin is not particularly limited, and examples thereof include a thermosetting resin and a thermoplastic resin.

[0185] The resin composition can be cured to form a cured product of the resin composition, and can be cured and molded to form a molded product of the resin composition. For molding, the resin composition can be appropriately subjected to treatments such as melting and kneading. Examples of molding methods include compression molding, injection molding, extrusion molding, and foam molding. Among them, extrusion molding using an extrusion molding machine is preferred, and extrusion molding using a twin-screw extruder is more preferred. When the resin composition is used as a coating agent, paint, or the like, the resin composition can be applied to an object to be coated to form a coating film having a cured product of the resin composition.

[0186] <Method of producing resin composition> According to one embodiment of the present invention, a method for producing a resin composition is provided.

[0187] The production method includes a step of mixing the composite particles with a resin. As the composite particles, those described above can be used, and therefore description thereof will be omitted here.

[0188] The composite particles used may be surface-treated.

[0189] The composite particles used may be of one type alone or in combination of two or more types.

[0190] Furthermore, the composite particles may be used in combination with other fillers (alumina, spinel, boron nitride, aluminum nitride, magnesium oxide, magnesium carbonate, etc.).

[0191] The content of the composite particles is preferably 5 to 95% by mass, more preferably 10 to 90% by mass, and even more preferably 30 to 80% by mass, based on 100% by mass of the resin composition. If the content of the composite particles is 5% by mass or more, the high thermal conductivity of the composite particles can be efficiently exhibited, which is preferable. On the other hand, if the content of the composite particles is 95% by mass or less, a resin composition with excellent moldability can be obtained, which is preferable. When the resin composition is used as a coating agent, paint, or the like, from the viewpoint of exhibiting excellent oxidation catalyst function, antibacterial and antiviral functions and facilitating the formation of a coating film, the content of the composite particles is preferably 0.1 to 80 mass%, more preferably 1 to 50 mass%, and even more preferably 3 to 30 mass%, relative to 100 mass% of the solid content of the resin composition.

[0192] (resin) The resin is not particularly limited, and examples thereof include thermoplastic resins and thermosetting resins.

[0193] The thermoplastic resin is not particularly limited, and known and commonly used resins used for molding materials, etc. can be used. Specific examples include polyethylene resin, polypropylene resin, polymethyl methacrylate resin, polyvinyl acetate resin, ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, polyvinyl chloride resin, polystyrene resin, polyacrylonitrile resin, polyamide resin, polycarbonate resin, polyacetal resin, polyethylene terephthalate resin, polyphenylene oxide resin, polyphenylene sulfide resin, polysulfone resin, polyether sulfone resin, polyether ether ketone resin, polyaryl sulfone resin, thermoplastic polyimide resin, thermoplastic urethane resin, polyamino bismaleimide resin, polyamide imide resin, polyether imide resin, bismaleimide triazine resin, polymethyl pentene resin, fluorinated resin, liquid crystal polymer, olefin-vinyl alcohol copolymer, ionomer resin, polyarylate resin, acrylonitrile-ethylene-styrene copolymer, acrylonitrile-butadiene-styrene copolymer, acrylonitrile-styrene copolymer, etc.

[0194] The thermosetting resin is a resin that has the property of becoming substantially insoluble and infusible when cured by means of heating, radiation, a catalyst, or the like, and generally, any known and commonly used resin used for molding materials, etc. may be used. Specific examples of the epoxy resin include novolac-type phenolic resins such as phenol novolac resin and cresol novolac resin; phenolic resins such as unmodified resol phenolic resin and resol-type phenolic resin such as oil-modified resol phenolic resin modified with tung oil, linseed oil, walnut oil, etc.; bisphenol-type epoxy resins such as bisphenol A epoxy resin and bisphenol F epoxy resin; novolac-type epoxy resins such as aliphatic chain-modified bisphenol-type epoxy resin, novolac epoxy resin, cresol novolac epoxy resin; epoxy resins such as biphenyl-type epoxy resin and polyalkylene glycol-type epoxy resin; resins having a triazine ring such as urea resin and melamine resin; vinyl resins such as (meth)acrylic resin and vinyl ester resin; unsaturated polyester resin, bismaleimide resin, polyurethane resin, diallyl phthalate resin, silicone resin, resin having a benzoxazine ring, cyanate ester resin, etc.

[0195] The above-mentioned resins may be used alone or in combination of two or more kinds. In this case, two or more kinds of thermoplastic resins may be used, two or more kinds of thermosetting resins may be used, or one or more kinds of thermoplastic resins and one or more kinds of thermosetting resins may be used.

[0196] The resin content is preferably 5 to 90% by mass, and more preferably 10 to 70% by mass, based on 100% by mass of the resin composition. A resin content of 5% by mass or more is preferable because it can impart excellent moldability to the resin composition. On the other hand, a resin content of 90% by mass or less is preferable because it can be molded into a compound with high thermal conductivity.

[0197] (hardening agent) If necessary, a curing agent may be mixed into the resin composition. The curing agent is not particularly limited, and any known curing agent may be used.

[0198] Specific examples include amine compounds, amide compounds, acid anhydride compounds, and phenol compounds.

[0199] Examples of the amine compounds include diaminodiphenylmethane, diethylenetriamine, triethylenetetramine, diaminodiphenylsulfone, isophoronediamine, imidazole, BF3-amine complexes, and guanidine derivatives.

[0200] Examples of the amide-based compound include dicyandiamide, and a polyamide resin synthesized from a dimer of linoleic acid and ethylenediamine.

[0201] Examples of the acid anhydride compound include phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, maleic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylnadic anhydride, hexahydrophthalic anhydride, and methylhexahydrophthalic anhydride.

[0202] Examples of the phenol-based compound include phenol novolac resin, cresol novolac resin, aromatic hydrocarbon formaldehyde resin modified phenol resin, dicyclopentadiene phenol addition type resin, phenol aralkyl resin (Zylok resin), polyhydric phenol novolac resin synthesized from a polyhydric hydroxy compound represented by resorcin novolac resin and formaldehyde, naphthol aralkyl resin, trimethylol methane resin, tetraphenylol ethane resin, naphthol novolac resin, naphthol-phenol co-condensed novolac resin, naphthol- Examples of polyhydric phenol compounds include cresol co-condensed novolac resins, biphenyl-modified phenol resins (polyhydric phenol compounds in which phenol nuclei are linked by bismethylene groups), biphenyl-modified naphthol resins (polyhydric naphthol compounds in which phenol nuclei are linked by bismethylene groups), aminotriazine-modified phenol resins (polyhydric phenol compounds in which phenol nuclei are linked by melamine, benzoguanamine, etc.), and alkoxy group-containing aromatic ring-modified novolac resins (polyhydric phenol compounds in which phenol nuclei and alkoxy group-containing aromatic rings are linked by formaldehyde).

[0203] The above curing agents may be used alone or in combination of two or more kinds.

[0204] (Cure accelerator) If necessary, a curing accelerator may be mixed into the resin composition.

[0205] The curing accelerator has the function of accelerating the curing of the composition.

[0206] The curing accelerator is not particularly limited, but examples thereof include phosphorus-based compounds, tertiary amines, imidazoles, organic acid metal salts, Lewis acids, and amine complex salts.

[0207] The above-mentioned curing accelerators may be used alone or in combination of two or more kinds.

[0208] (curing catalyst) If necessary, a curing catalyst may be mixed into the resin composition.

[0209] The curing catalyst functions to promote the curing reaction of a compound having an epoxy group in place of the curing agent.

[0210] The curing catalyst is not particularly limited, and a known and commonly used thermal polymerization initiator or active energy ray polymerization initiator can be used.

[0211] The curing catalyst may be used alone or in combination of two or more kinds.

[0212] (Viscosity modifier) A viscosity modifier may be mixed into the resin composition, if necessary.

[0213] The viscosity modifier functions to adjust the viscosity of the composition.

[0214] The viscosity modifier is not particularly limited, and organic polymers, polymer particles, inorganic particles, etc. can be used.

[0215] The viscosity modifiers may be used alone or in combination of two or more kinds.

[0216] (Plasticizer) A plasticizer may be mixed into the resin composition, if necessary.

[0217] The plasticizer has the function of improving the processability, flexibility, weather resistance, etc. of the thermoplastic synthetic resin.

[0218] The plasticizer is not particularly limited, and examples of the plasticizer that can be used include phthalates, adipates, phosphates, trimellitates, polyesters, polyolefins, and polysiloxanes.

[0219] The above-mentioned plasticizers may be used alone or in combination of two or more kinds.

[0220] [Mixing process] The resin composition according to the present embodiment can be obtained by mixing the composite particles, the resin, and, if necessary, other ingredients. There is no particular limitation on the mixing method, and the mixture can be mixed by a known, commonly used method.

[0221] When the resin is a thermosetting resin, a typical method for mixing the thermosetting resin with the composite particles, etc., is to thoroughly mix a predetermined amount of the thermosetting resin, the composite particles, and other components as necessary with a mixer, etc., and then knead with a three-roll mill, etc., to obtain a fluid liquid composition. In another embodiment, a method for mixing the thermosetting resin with the composite particles is to thoroughly mix a predetermined amount of the thermosetting resin, the composite particles, and other components as necessary with a mixer, etc., and then melt-knead with a mixing roll, extruder, etc., and then cool to obtain a solid composition. Regarding the mixed state, when a curing agent, catalyst, etc. are blended, it is sufficient that the curable resin and the blended material are mixed sufficiently uniformly, but it is more preferable that the composite particles are also uniformly dispersed and mixed.

[0222] In the case where the resin is a thermoplastic resin, a general method of mixing the thermoplastic resin with the composite particles, etc., is to mix the thermoplastic resin, the composite particles, and other components as necessary in advance using various mixers such as a tumbler or a Henschel mixer, and then melt-knead using a mixer such as a Banbury mixer, a roll, a Brabender, a single-screw kneading extruder, a twin-screw kneading extruder, a kneader, a mixing roll, etc. The temperature for melt-kneading is not particularly limited, but is usually in the range of 100 to 320°C.

[0223] A coupling agent may be added externally to the resin composition, since this can further increase the fluidity of the resin composition and the filler loading of the composite particles, etc. By adding a coupling agent externally, the adhesion between the resin and the composite particles can be further increased, the interfacial thermal resistance between the resin and the composite particles can be reduced, and the thermal conductivity of the resin composition can be improved.

[0224] The above-mentioned coupling agents may be used alone or in combination of two or more kinds.

[0225] The amount of the coupling agent added is not particularly limited, but is preferably 0.01 to 5 mass %, and more preferably 0.1 to 3 mass %, relative to the mass of the resin.

[0226] The molybdenum oxide constituting the inorganic coating portion of the composite particle is excellent in antibacterial properties, antiviral properties, and oxidation catalyst function. The plate-like alumina particles constituting the composite particle are excellent in mechanical properties, and the molybdenum oxide contained in the plate-like alumina particles is excellent in oxidation catalyst function, etc. Therefore, the resin composition is suitably used as a coating agent, paint, etc. that can impart one or more of the above functions and properties.

[0227] The resin composition can also be used as a thermally conductive material. The plate-like alumina particles contained in the resin composition have excellent thermal conductivity, so the resin composition can also be used as an insulating heat dissipation member. This can improve the heat dissipation function of the device, contributing to making the device smaller, lighter, and more powerful.

[0228] <Method of manufacturing the cured product> According to one embodiment of the present invention, there is provided a method for producing a cured product, which comprises curing the resin composition produced as described above.

[0229] The curing temperature is not particularly limited, but is preferably from 20 to 300°C, and more preferably from 50 to 200°C.

[0230] The curing time is not particularly limited, but is preferably 0.1 to 10 hours, and more preferably 0.2 to 3 hours.

[0231] The shape of the cured product varies depending on the desired application, and can be appropriately designed by those skilled in the art.

[0232] In this embodiment, the alumina particles are plate-like alumina particles, and the composite particles also have a plate shape, but this is not limited thereto, and the alumina particles may be polyhedral alumina particles, and the composite particles may have a polyhedral shape.

[0233] In addition, in the above-described resin composition, method for producing the resin composition, and cured product, composite particles having a plate-like shape are used, but this is not limited thereto, and composite particles having a polyhedral shape may also be used. EXAMPLES

[0234] The following describes examples of the present invention, but the present invention is not limited to the following examples.

[0235] <Example 1> First, alumina particles were produced as the base of the composite particles. 120 g of aluminum hydroxide (manufactured by Nippon Light Metals Co., Ltd., average particle size 1 to 2 μm) (90 mass% in terms of oxide of Al2O3), 7.8 g of molybdenum trioxide (manufactured by Taiyo Koko Co., Ltd.) (9 mass% in terms of oxide of MoO3), and 0.78 g of silicon dioxide (manufactured by Kanto Chemical Co., Ltd., special grade) (1 mass% in terms of oxide of SiO2) were mixed in a mortar to obtain a mixture. The obtained mixture was placed in a crucible, heated to 1100°C at 5°C / min in a ceramic electric furnace, and held at 1100°C for 5 hours to perform firing. After that, the temperature was lowered to room temperature at 5°C / min, and the crucible was removed to obtain 79.0 g of a powder of plate-shaped alumina A.

[0236] 10.0 g of the obtained powder of alumina particles A was dispersed in 50 mL of ethanol, and the dispersion was stirred at room temperature (25 to 30° C.) for 3 hours, and then the ethanol was removed by filtration. The resulting mixture was dried to obtain 9.9 g of powder of alumina particles B1.

[0237] 2 g of the obtained alumina particle B1 powder and 0.8 g of molybdenum trioxide (molybdenum trioxide synthesized in Example 1 of WO 2021 / 060375) were mixed to obtain a mixture. The obtained mixture was placed in a crucible, heated to 800 ° C. at 5 ° C. / min in a ceramic electric furnace, and held at 800 ° C. for 5 hours for firing. After that, the temperature was lowered to room temperature at 5 ° C. / min, and the crucible was removed to obtain 2.5 g of composite particle powder.

[0238] <Example 2> 2.2 g of composite particle powder was obtained by the same method as in Example 1, except that 2 g of alumina particle B1 powder after washing with ethanol was mixed with 0.4 g of molybdenum trioxide (molybdenum trioxide synthesized in Example 1 of WO 2021 / 060375) to obtain a mixture.

[0239] <Example 3> 5.15 g of composite particle powder was obtained by the same method as in Example 1, except that 5 g of alumina particle B1 powder after washing with ethanol was mixed with 0.5 g of molybdenum trioxide (molybdenum trioxide synthesized in Example 1 of WO 2021 / 060375) to obtain a mixture.

[0240] <Example 4> 5.0 g of composite particle powder was obtained by the same method as in Example 1, except that 5 g of alumina particle B1 powder after washing with ethanol was mixed with 0.25 g of molybdenum trioxide (molybdenum trioxide synthesized in Example 1 of WO 2021 / 060375) to obtain a mixture.

[0241] <Example 5> A mixture was obtained by mixing 5 g of the powder of alumina particles B1 after washing with ethanol with 1.0 g of molybdenum trioxide (manufactured by Taiyo Koko Co., Ltd.). The mixture was placed in a crucible and heated to 900°C at 5°C / min in a ceramic electric furnace, and then held at 900°C for 5 hours for firing. After that, the temperature was lowered to room temperature at 5°C / min, and the crucible was removed to obtain 5.15 g of composite particle powder.

[0242] <Example 6> A mixture was obtained by mixing 5 g of the powder of alumina particles B1 after washing with ethanol with 1.0 g of molybdenum trioxide (manufactured by Taiyo Koko Co., Ltd.). The mixture was placed in a crucible and heated to 1000°C at 5°C / min in a ceramic electric furnace, and then held at 1000°C for 5 hours for firing. After that, the temperature was lowered to room temperature at 5°C / min, and the crucible was removed to obtain 5.10 g of composite particle powder.

[0243] <Comparative Example 1> As Comparative Example 1, a powder of alumina particles A in a state before being washed with ethanol was obtained by the same production method as in Example 1. The SEM image of the obtained powder is shown in Figure 3. The magnification of Figure 3 is 2000 times. The SEM observation showed that the shape of alumina particle A was polygonal, the thickness was 400 nm, and the particle size distribution measurement showed that the diameter of alumina particle A was 1.0 mm. 50 It was confirmed that the grain size was 5 μm and the aspect ratio was 12.5. Furthermore, when an XRD measurement was performed, a sharp scattering peak derived from α-alumina appeared, and no alumina crystallographic peaks other than the α crystal structure were observed, confirming that the α crystallization rate was 99% or more.

[0244] <Comparative Example 2> As Comparative Example 2, a powder of alumina particles B1 in a state after washing with ethanol was obtained by the same production method as in Example 1.

[0245] <Comparative Example 3> As Comparative Example 3, alumina particles B2 in a state after washing with water were obtained by the same production method as in Example 1. 9.8 g of alumina particles B2 powder was obtained by the same production method as in Example 1, except that a dispersion liquid was prepared by dispersing 10.0 g of the alumina particles A powder obtained in Example 1 in 50 mL of water.

[0246] Evaluation [Measurement of the long diameter L of alumina particles] Using a laser diffraction particle size measurement device (Shimadzu Corporation, SALD-7000), 1 mg of alumina powder was diluted with a 0.2 wt% aqueous solution of sodium hexametaphosphate (Fujifilm Wako Pure Chemical Industries, Ltd.) to a total of 18 g, and this was used as a sample for measurement. The average particle size D 50 The value (μm) was determined as the major axis L.

[0247] [Measurement of thickness D of alumina particles] A scanning electron microscope (SEM) was used to measure the thickness of 50 pieces, and the average value was used as the thickness D (μm).

[0248] [Aspect ratio L / D] The aspect ratio was calculated using the following formula. (Aspect ratio) = (long axis of alumina particle L / thickness of alumina particle D)

[0249] [XRF analysis] Using an X-ray fluorescence (XRF) analyzer (Rigaku Corporation, Primus IV), approximately 70 mg of the powder sample was placed on filter paper, covered with PP film, and subjected to composition analysis. The amount of Al2O3 ([Al2O3]), SiO2 ([SiO2]) and MoO3 ([MoO3]) was obtained by X-ray fluorescence (XRF) analysis, and the ratio of the amount of MoO3 to the amount of Al2O3 in the alumina particles ([MoO3] / [Al2O3]×100) was calculated. XRF asked for.

[0250] [XPS analysis] The prepared sample (composite particles) was pressed and fixed onto double-sided tape using an X-ray photoelectron spectroscopy (XPS) device (ULVAC-PHI, Quantera SXM), and composition analysis was performed under the following conditions. X-ray source: Monochromatic AlKα, beam diameter 100μmφ, output 25W Measurement: Area measurement (1000 μm square), n=3 Charge correction: C1s=284.8eV The amount of Al2O3 ([Al2O3]), SiO2 ([SiO2]) and MoO3 ([MoO3]) was obtained by X-ray photoelectron spectroscopy (XPS) analysis, and the ratio of the amount of MoO3 to the amount of Al2O3 on the surface of the alumina particles ([MoO3] / [Al2O3]×100) was calculated. XPS asked for.

[0251] [pH measurement of aqueous dispersion] 0.1 g of each of the composite particle powders obtained in Examples 1 to 6 and Comparative Examples 1 to 3 was dispersed in 9.9 mL of water to prepare a dispersion, and the pH of each dispersion was measured using a pH measuring device (HORIBA Scientific, LAQUA act portable type D-71). The results are shown in Table 1.

[0252] [Table 1]

[0253] First, SEM images of the composite particles obtained in Examples 1 and 4 are shown in Fig. 1 and Fig. 2, respectively. The magnifications of Fig. 1 and Fig. 2 are 1000 times and 2000 times, respectively. From Fig. 1 and Fig. 2, it was confirmed that the composite particles of Examples 1 and 4 were plate-shaped.

[0254] In addition, from the results in Table 1, the ratio of the amount of MoO3 to the amount of Al2O3 on the surface of the alumina particles ([MoO3] / [Al2O3]×100) XPS The molybdenum oxide content was 47, indicating that a large amount of molybdenum oxide was present on the surface of the alumina particles as an inorganic coating. Furthermore, ([MoO3] / [Al2O3]×100) XRF It was found that the amount of molybdenum oxide present on the surface of the alumina particles was 43, and that the amount of molybdenum oxide present on the surface of the alumina particles was greater than the amount of molybdenum oxide present in the entire alumina particles.

[0255] In Example 2, the ratio of the amount of MoO3 to the amount of Al2O3 on the surface of the alumina particles ([MoO3] / [Al2O3]×100) XPSThe value of ([MoO3] / [Al2O3]×100) was 32, and it was found that a large amount of molybdenum oxide was present on the surface of the alumina particles, similar to Example 1. XRF It was found that the amount of molybdenum oxide present on the surface of the alumina particles was greater than the amount of molybdenum oxide present in the entire alumina particles.

[0256] In Example 3, the ratio of the amount of MoO3 to the amount of Al2O3 on the surface of the alumina particles ([MoO3] / [Al2O3]×100) XPS The molybdenum oxide content was 27, which was similar to that in Example 1. It was found that a large amount of molybdenum oxide was present on the surface of the alumina particles. In addition, ([MoO3] / [Al2O3]×100) XRF It was found that the amount of molybdenum oxide present on the surface of the alumina particles was greater than the amount of molybdenum oxide present in the entire alumina particles.

[0257] In Example 4, the ratio of the amount of MoO3 to the amount of Al2O3 on the surface of the alumina particles ([MoO3] / [Al2O3]×100) XPS The molybdenum oxide content was 24, indicating that a large amount of molybdenum oxide was present on the surface of the alumina particles. In particular, ([MoO3] / [Al2O3]×100) XRF It was found that the amount of molybdenum oxide present on the surface of the alumina particle was 4, and that the amount of molybdenum oxide present on the surface of the alumina particle was far greater than the amount of molybdenum oxide present in the entire alumina particle.

[0258] In Example 5, the ratio of the amount of MoO3 to the amount of Al2O3 on the surface of the alumina particles ([MoO3] / [Al2O3]×100) XPS The molybdenum oxide content was 22, indicating that a large amount of molybdenum oxide was present on the surface of the alumina particles. In particular, ([MoO3] / [Al2O3]×100) XRF was 1.2, and it was found that the amount of molybdenum oxide present on the surface of the alumina particle was far greater than the amount of molybdenum oxide present in the entire alumina particle.

[0259] In Example 6, the ratio of the amount of MoO3 to the amount of Al2O3 on the surface of the alumina particles ([MoO3] / [Al2O3]×100) XPS The value of ([MoO3] / [Al2O3]×100) was 19, indicating that a large amount of molybdenum oxide was present on the surface of the alumina particles. XRF was 1.3, and it was found that the amount of molybdenum oxide present on the surface of the alumina particle was far greater than the amount of molybdenum oxide present in the entire alumina particle.

[0260] Moreover, the dispersions in which the composite particles of Examples 1 to 6 were dispersed had a low pH of 3.9 to 4.8.

[0261] On the other hand, in Comparative Example 1, the ratio of the amount of MoO3 to the amount of Al2O3 on the surface of the alumina particles ([MoO3] / [Al2O3]×100) XPS was 13, which was smaller than any of Examples 1 to 6. In addition, ([MoO3] / [Al2O3]×100) XRF was 0.6, which was smaller than any of Examples 1 to 6.

[0262] In Comparative Example 2, the ratio of the amount of MoO3 to the amount of Al2O3 on the surface of the alumina particles ([MoO3] / [Al2O3]×100) XPS was 8, which was smaller than any of Examples 1 to 6, as was Comparative Example 1. In addition, ([MoO3] / [Al2O3]×100) XRF was 0.7, which was smaller than any of Examples 1 to 6.

[0263] In Comparative Example 3, the ratio of the amount of MoO3 to the amount of Al2O3 on the surface of the alumina particles ([MoO3] / [Al2O3]×100) XPS was 2, which was smaller than any of Examples 1 to 6, as was Comparative Example 1. In addition, ([MoO3] / [Al2O3]×100) XRF was 0.3, which was smaller than any of Examples 1 to 6.

[0264] Moreover, the dispersions in which the alumina particles of Comparative Examples 1-3 were dispersed had a pH of 5.0 to 6.8, which was higher than any of the dispersions in Examples 1-6.

Claims

1. The inorganic coating portion includes alumina particles and an inorganic coating portion formed on a surface of the alumina particles and composed of molybdenum oxide, The alumina particles contain silicon and / or germanium and further contain mullite in a surface layer, Al on the surface of the alumina particles obtained by X-ray photoelectron spectroscopy (XPS) analysis 2 O 3 MoO for quantity 3 The ratio of the amount ([MoO 3 ] / [Al 2 O 3 ]×100) XPS of 15 or more.

2. The Al content of the alumina particles obtained by X-ray fluorescence (XRF) analysis 2 O 3 MoO for quantity 3 The ratio of the amount ([MoO 3 ] / [Al 2 O 3 ] x 100) XRF is 1 or greater; ([MoO 3 ] / [Al 2 O 3 ]×100) XPS is ([MoO 3 ] / [Al 2 O 3 ]×100) XRF.

3. The composite particle according to claim 1 or 2, wherein the alumina particle has an alpha crystallization rate of 90% or more.

4. The composite particle according to any one of claims 1 to 3, wherein the alumina particle contains molybdenum.

5. The composite particle according to any one of claims 1 to 4, wherein the alumina particles have a plate shape, a thickness of 0.01 µm or more and 5 µm or less, an average particle diameter of 0.1 µm or more and 500 µm or less, and an aspect ratio of 2 or more and 500 or less.

6. A process for producing alumina particles having mullite on a surface layer by firing a first mixture containing an aluminum compound containing an aluminum element, a molybdenum compound containing a molybdenum element, and a shape control agent for controlling the shape of alumina particles, the shape control agent being composed of one or more selected from silicon, a silicon compound containing a silicon element, and a germanium compound containing a germanium element; a step of firing a second mixture containing the alumina particles and a molybdenum compound containing elemental molybdenum to form an inorganic coating portion composed of a molybdenum compound on the surface of the alumina particles; A method for producing composite particles, comprising:

7. The method for producing composite particles according to claim 6 , wherein the molybdenum compound is molybdenum oxide.

8. The method for producing composite particles according to claim 7 , wherein the second mixture is fired at 750° C. or higher and lower than 1100° C. in the step of forming the inorganic coating portion.

9. The method for producing composite particles according to claim 7 , wherein the first mixture is fired at 900° C. or higher in the step of producing the alumina particles.

10. The method for producing composite particles according to any one of claims 6 to 9, wherein the first mixture further contains a potassium compound containing potassium element.

Citation Information

Patent Citations

  • Pigment for hydrogen embrittlement-preventing coating and coating material containing same

    JP1989313571A

  • Process for mildly hydrocracking heavy hydrocarbon feedstock using silica-alumina catalyst

    JP1996003568A

  • New catalystic composition, its production and hydrotreatment of hydrocarbon oil using catalystic composition

    JP1997164333A

  • Absorbent material of metal mercury in exhaust gas and method for removing metal mercury using it

    JP2008238057A

  • Tabular alumina particle and production method thereof

    JP2016222501A